An Improved Proportional Resonant Controller for Current Harmonics Reduction and Power Ripples Mitigation of Self-Synchronized Grid-tied PV System under Distorted Grid Voltages - Mishra M.K.; Lal V.N. (My University, 2025)
This paper presents a phase-locked loop less (PLL-less) control scheme (PLCS) with an improved proportional resonant (IPR) controller for a grid-tied solar photovoltaic system (GTPVS). The proposed control scheme operates in a self-synchronized mode without the need of a PLL block. This reduces the computational burden on the controller and eliminates the delay due to the PLL block. In addition, it also improves the dynamic performance of the GTPVS under grid frequency deviations. The improved proportional resonant (IPR) controller reduces grid current harmonics under distorted grid voltages. Further, this control scheme is utilized to eliminate the active and reactive power ripples during grid fault or sag conditions. In order to extract the maximum power from photovoltaic (PV) array, a variable step-size incremental conductance (VSS-INC) maximum power point tracking (MPPT) algorithm is implemented. Real-time experiments are carried out using OPAL-RT real-time simulator to verify the effectiveness of the proposed PLCS compare to the conventional PLL-based control scheme (PBCS). © 2021 IEEE.